Conventional gene stacking as a strategy to improve chickpea resistance to Ascochyta blight - Alaskar, Basel; Khatib, Fateh; Al-Daoude, Antonious (Frontiers in Plant Science, 2026)
The main disease that affects chickpea production worldwide is Aschochyta blight (AB), caused by the fungus Aschochyta rabiei. The identification of cultivars with stacking resistance genes is crucial for controlling these diseases. This work aimed to evaluate the effect of stacking two resistance-related genes, chitinase and vst-1, on disease response in chickpea (Cicer arietinum L.). Gene stacking was achieved through conventional hybridization between three transgenic inbred lines: N292 and N346 (both carrying chitinase), and N52 (carrying vst-1). PCR confirmed the stable inheritance of both transgenes in F1 and F2 generations, although segregation ratios deviated from Mendelian expectations. Functional assays were conducted using protein extracts to test inhibition of fungal spore germination and mycelium formation, followed by detached-leaf and whole-plant infection assays. Protein extracts from stacked lines significantly reduced spore germination (up to 90% inhibition, P < 0.01) and suppressed mycelium development compared to controls. Detached-leaf assays revealed a reduced disease severity in stacked lines (mean DS = 74 vs. 89 in controls), while whole-plant assays confirmed lower severity scores (mean 4–6 vs. 8 in controls) despite no reduction in infection incidence. The hybrid N346 × N52 exhibited the strongest resistance phenotype across assays. These results demonstrate that stacking chitinase and vst-1 increases tolerance to A. rabiei in chickpea by reducing disease severity, providing a promising strategy for developing tolerant cultivars. This study is a successful tool for developing gene stacking technology in crops to contribute to improving the resistance of chickpea plants to Ascochyta disease.